2007
DOI: 10.4314/as.v4i1.1526
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fertilizer rates and cutting frequency on the marketable vegetable and pod yields in fluted pumpkin in southeastern Nigeria

Abstract: Field plot studies were conducted on the effects of fertilizer rates and frequencies of cut on fluted pumpkin (Telfairia occidentatis) growth and yield parameters. Treatments comprised four levels of commercial N 20 P 10 K 10 and four cutting intervals. These were laid out in a randomized complete block design with three replications. The experiment was conducted at Nsukka which is located at Latitude 06 0 52'N, longitude 07 0 24't, and on altitude 447.2m above sea level. The site was characterized as tropical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 5 publications
(7 reference statements)
3
11
0
Order By: Relevance
“…The increase in number of branches after first harvest at 3 WAT was as a result of apical dominance removal which resulted in new branch flushes. Ogar and Asiegbu (2005) reported high leaf yield and number of branches in fluted pumpkin as a result of apical dominance removal. The reduced increase in these plant parts from 5 to 7 WAT suggested increased deposit in the vine portion which resulted in improved vine diameter and length.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in number of branches after first harvest at 3 WAT was as a result of apical dominance removal which resulted in new branch flushes. Ogar and Asiegbu (2005) reported high leaf yield and number of branches in fluted pumpkin as a result of apical dominance removal. The reduced increase in these plant parts from 5 to 7 WAT suggested increased deposit in the vine portion which resulted in improved vine diameter and length.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that some production techniques could affect fluted pumpkin yield. These include time of sowing (Asiegbu ), tillage practice (Awodun ), manure rate (Ogar and Asiegbu ; Awodun ), plant staking (Egun ; Chukwudi and Agbo ), and cutting frequency (Ogar and Asiegbu ; Chukwudi and Agbo ). In Nigerian savanna where bulk of agriculture is done, low status of plant nutrients and poor soil physical condition constitute serious agronomic constraints (Salako ).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the highest number of fruit per plant, fruit weight per plant and fruit yield recorded by the highest amount of fertilizers rates could be explained by the favourable impact of fertilization on fruit process production [9,10]. This increase in productivity of plants according to fertilizer rates was also shown by Vijaya and Halakshmi [11].…”
Section: Fruit Number Per Plant Fruit Weight Per Plant and Fruit Yieldmentioning
confidence: 65%